RURAL WOMEN’S APPLICATION OF THE TECHNICAL RECOMMENDATIONS RELATED TO BREEDING AND CARE OF DAIRY CATTLE IN SOME VILLAGES OF KAFRELSHEIKH GOVERNORATE - Awad, Mayada Al - Shawadfi; Al - Dumeiri, Izzat Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2019)
The main objective of this research was to study rural women’s application for the technical recommendations related to breeding and care of dairy cattle in some villages of kafrelshiekh governorate. Sample size amounted to 346 respondents were selected from three villages in three districts in a simple random way as a standard criterion for selection, the villages were selected are: Gama moon from Desouq district, Meniat Meseer from kafrelshiekh district, and the village of ElKafr Elbahary from Killeen district. The most important results were; the level of implementation of the rural respondents for the technical recommendations related to feeding of milk Cattle and technical recommendations related to preparation of milking & milk production was moderate, while their implementation level of technical recommendations for the health care of dairy cattle was high. The most important reasons for not execute of the rural women respondents for the technical recommendations related to care of dairy cattle in the three studied areas were: high prices of fodder or breeding inputs, or because the rural women respondents have false and incorrect information, or because the correct information is not available to them. The most important sources of information which the rural women respondents were depending on to obtain information related to the care of dairy cattle were: their personal experiences, veterinarian, mother or mother-in-law, and the husband.